Tissue Resident Memory γδT Cells in Murine Uterus Expressed High Levels of IL-17 Promoting the Invasion of Trophocytes - Kang, Shuangpeng; Wu, Qiongli; Huang, Jun; Yang, Binyan; Liang, Changyan; Chi, Peidong; Wu, Changyou (Frontiers in Immunology, 2021)
γδT cells are non-conventional T cells and serve as the bridge for connecting the innate and adaptive immune systems. γδT cells form a substantial population at barrier sites and play an important role in the development of physiology, inflammation, autoimmune diseases and tumors. γδT cells not only distribute in the maternal-fetal interface during pregnancy but also in non-pregnant uterus. However, the phenotypes and functions of γδT cells in uterus were not clear. In the current study, we found that the percentages of γδT cells were significantly higher in murine uterus than peripheral blood and most of γδT cells in uterus were distributed in endometrium. Further studies indicated that the majority of γδT cells in uterus were memory cells with higher expression of CD44 and CD27 but lower expression of CD62L and CCR7 compared to those in blood. In addition, we found that γδT cells in uterus were tissue resident memory γδT cells expressing CD69, expressed high levels of CCR6, GranzymeB and CD107a. Moreover, γδT cells in uterus were activated and fully expressed transcription factor RORγt. After short time of activation, γδT cells in uterus significantly expressed high levels of IL-17 but not IFN-γ, which promotes the invasion of murine trophocytes. Taken together, our study will lay the foundation for future research on uterine γδT cells in pregnancy and autoimmune disease.